Unison Source Separation - Stöter, Fabian-Robert; Bayer, Stefan; Edler, Bernd (17th International Conference on Digital Audio Effects (DAFx-14), 2014)
In this work we present a new scenario of analyzing and separating linear mixtures of musical instrument signals. When instruments are playing in unison, traditional source separation methods are not performing well. Although the sources share the same pitch, they often still differ in their modulation frequency caused by vibrato and/or tremolo effects. In this paper we propose source separation schemes that exploit AM/FM characteristics to improve the sep- aration quality of such mixtures. We show a method to process mixtures based on differences in their amplitude modulation fre- quency of the sources by using non-negative tensor factorization. Further, we propose an informed warped time domain approach for separating mixtures based on variations in the instantaneous frequencies of the sources.